DaHijab / Muhammad Jafni Muhsin Mohd Nizam, Muhammad Waqiyuddin Azmi and Muhamad Aiman Danial Rosli - Mohd Nizam, Muhammad Jafni Muhsin; Azmi, Muhammad Waqiyuddin; Rosli, Muhamad Aiman Danial (2022)
This business is called DaHijab, and it is owned by Muhammad Waqiyuddin Bin Azmi, Muhamad Aiman Danial Bin Rosli, Muhammad Jafni Muhsin Bin Mohd Nizam. It specialises in 'Muslimah Fashion Style.' He is now pursuing a Bachelor of Business Administration with honours. Because to Covid-19, they are currently looking for part-time jobs to supplement their income while they study. As a result, they came up with an idea and decided to start a business together named DaHijab on the online platform, Facebook. DaHijab is an online business that started solely on Facebook. It was established in the year 2021 and is focusing on fashion and lifestyle products. Because simplicity in clothing is currently trendy, they decided to market hijab, which is a simple and modest garment that is popular among women DaHijab has launched a Facebook page to expand its business platform and attract a wider audience. Facebook is widely acknowledged as one of the most effective social media channels for helping merchants communicate with their consumers and engage with potential purchasers. Soft sells, hard sells, and first teasers can all be done effectively on the platform. DaHijab sells two varieties of hijabs which are Bawal Cotton Premium, which is their most popular item, and Satin Shawl. The customer reaction on these two hijabs has been overwhelmingly good. Many individuals, including their family and friends, encouraged and supported them in their quest.